Peak Running Velocity or Critical Speed Under Field Conditions: Which Best Predicts 5-km Running Performance in Recreational Runners? - Figueiredo, Diogo Hilgemberg; Figueiredo, Diego Hilgemberg; Manoel, Francisco de Assis; Machado, Fabiana Andrade (Frontiers in Physiology, 2021)
This study aimed to examine which variable, between the peak running velocity determined on the track field (Vpeak_TF) and critical speed (CS), is the best predictor of the 5-km running performance in recreational runners. Twenty-five male performed three tests to determine the Vpeak_TF, CS, and 5-km running performance on the track field; with a minimal interval of 48 hours between each test. The Vpeak_TF protocol started with a velocity of 8 km.h−1, followed by an increase of 1 km.h−1 every three minutes until volitional exhaustion, which was controlled by sound signals, with cones were at every 25 m, indicating when the participants were required to pass the cones' position to maintain the required velocity. The participants performed three time trials (TT) (1-2600, 2-1800, and 3-1000 m) on the same day, with a 30-minute rest period to determine the CS through the combinations of three (CS1,2,3) and two TT (CS1,2, CS1,3, and CS2,3). The 5-km running performance time was recorded to determine the test duration, and the mean velocity (MV) was calculated. There was a significant difference observed between the Vpeak_TF and the MV 5-km running performance. However, no differences were found between the CS values and the MV 5-km running performance. It was observed a correlation between the Vpeak_TF (R = -0.90), CS1,2,3 (R = -0.95), CS1,3 (R = -0.95) and the 5-km running performance time. Linear regression indicated that the Vpeak_TF (R2 = 0.82), CS1,2,3 (R2 = 0.90), and CS1,3 (R2 = 0.90) significantly predicted the 5-km running performance time. The CS results showed a higher prediction power for the 5-km running performance, slightly better than the Vpeak_TF. Also, the CS1,2,3 and the CS1,3 presented the highest predictive power for the 5-km running performance of recreational runners.